Optimizing extraction timing and characterizing the sex pheromone profile of the fall armyworm (Spodoptera frugiperda) in Indonesia - VANI NUR OKTAVIANY SUBAGYO; RAFIKA YUNIAWATI; PURNAMA HIDAYAT; DADANG DADANG; HERY WIDYANTO; I MADE SAMUDRA (Society for Indonesian Biodiversity, 2026)
Abstract. Subagyo VNO, Yuniawati R, Hidayat P, Dadang, Widyanto H, Samudra IM. 2026. Optimizing extraction timing and characterizing the sex pheromone profile of the fall armyworm (Spodoptera frugiperda) in Indonesia. Biodiversitas 27 (2): d270238. https://doi.org/10.13057/biodiv/d270238. The fall armyworm (Spodoptera frugiperda) threatens maize production in Indonesia, highlighting the need for pheromone tools tuned to local populations. We defined an operational extraction window and quantified the gland pheromone profile of Indonesian FAW females as a baseline for lure development. Virgin females from nine populations were sampled across age (1-4 days) and time after scotophase onset (2-6 hours). Pheromone glands were extracted in hexane and analyzed by GC-FID for three acetate components (Z7-12:OAc, Z9-14:OAc, Z11-16:OAc). In total, 130 extract vials (286 females pooled at 1-3 per vial) were analyzed; the vial was treated as the experimental unit and amounts were expressed as ng per gland. Total pheromone yield showed a consistent mid-scotophase ridge (generally 3-6 hours after lights-off), most apparent in 2-3-day-old females. A linear mixed model on log10(Total_ng) with Population as a random intercept detected a significant Age×Hour interaction (LRT χ²: 19.176, df: 10, p: 0.0381). Cells were ranked by mean Total_ng while prioritizing replication (n_vials ≥3) and population coverage; the selected global window was 3 days, 5 hours. Within this window, composition was consistently Z9-major (mean±SD: 80.18±13.61% Z9-14:OAc; 16.15±13.44% Z11-16:OAc; 3.67±5.31% Z7-12:OAc; n: 28 vials). These results provide a reproducible extraction standard and a locally derived reference blend (≈80:16:4) for subsequent behavioral assays and multi-site field validation.